ナンキョク マクマードサウンド カラ エラレタ フェラードレライト ノ コチジキ - 船木, 實; フナキ, ミノル; Funaki, Minoru (1983)
P(論文) 南極・マクマードサウンドのライト谷, アランヒルズ, カラペースヌナターク, それにフレミング山に分布する, フェラードレライトの岩床と岩脈から, 古地磁気学用試料を採集した。これらの試料に対し, 交流消磁および熱消磁を行い, 自然残留磁気の安定性を調べ, またヒステレシスおよび熱磁化特性も調べた。その結果, ライト谷, アランヒルズそれにフレミング山の試料は, 非常に安定な自然残留磁気を持つが, カラペースヌナタークのそれは, あまり安定でない。カラペースヌナタークの試料中の磁性粒子はおそらく擬単磁区あるいは多磁区構造を持ち, その他の試料のそれは, 単磁区あるいは擬単磁区構造を持つと推定される。測定されたすべての試料は正帯磁を示し, 計算される古磁極の値は, ライト谷 : 45.3°S・152.0°W, アランヒルズ : 47.0°S・133.2°W, フレミング山 : 68.6°S・139.5°W, である。これらの古磁極の値は, 今まで南極から得られたジュラ紀の古磁極の値と一致する。また今回得られたカラペースヌナタークを除く3個のVGPの値と, 今までに得られた7個のVGPから計算されるVGPの中心位置は, 南緯53.9°, 西経141.8°である。 Paleomagnetic samples were collected from a sill and dykes of Ferrar dolerite of the Jurassic age in the Wright Valley, the Allan Hills, the Carapace Nunatak and Mt. Fleming of the McMurdo Sound region. The stability of the natural remanent magnetization (NRM) of these samples was tested against the alternating field (AF) and thermal demagnetization, and the hysteresis and thermomagnetic properties were also measured. The overall results show that the samples from the Wright Valley, the Allan Hills and Mt. Fleming have a reasonably stable NRM; the samples from the Carapace Nunatak were less stable. The NRM carriers are inferred to have a pseudosingle or multi domain structure for the samples from Carapace Nunatak and a single or pseudosingle domain structure for others. All these samples were magnetized to the normal polarity, and the calculated VGP positions were 45.3°S・152.0°W for the Wright Valley, 47.0°S・133.2°W for the Allan Hills and 68.6°S・139.5°W for Mt. Fleming. The virtual geomagnetic pole (VGP) positions obtained in this study are in reasonable agreement with other Jurassic VGPs from Antarctica. The mean VGP center obtained from three values in this study, excluding that of the Carapace Nunatak, and from seven values in the previous studies is located at 53.9°S of latitude and 141.8°W of longitude for Ferrar dolerite. departmental bulletin paper